Synthesis of linear alkyl benzenes over zirconia-supported 12-molybdophosphoric acid catalysts - Devassy, Biju M.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction, and P-31 MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. 3 1 P MAS NMR spectra show that the nature of phosphorous species depend on MPA loading and calcination temperature, and it show the existence of three types of phosphorous species, one is the Keggin unit and the other is the decomposition product of MPA and third one an unidentified species. FTIR pyridine adsorption on 15% MPA catalyst calcined at 700 degrees C showed the presence both Bronsted and Lewis acidity. Under the reaction conditions of 83 C, benzene/1-olefin molar ratio of 10 (time, 1 h), the most active catalyst, 15% MPA calcined at 700 C gave more than 90% olefin conversion with selectivity to 2-phenyl octane, 55% and 2-phenyl dodecane, 45%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; benzene alkylation; linear alkyl benzene; Zirconia